Does Quality Assurance of Hotel Horison GKB Gresik East Java Matters Affecting Customer Loyalty? - Irene Indri Dewi Astuti; Sugiarto Sugiarto; Tonny Hendratono; Fongnawati Budhijono; Sutrisno Sutrisno (Badan Penerbit STIEPARI Press, 2025)
In the era of increasingly competitive hospitality industry, the implementation of Quality Assurance has become a strategic factor in ensuring the quality of hospitality services in line with the company's quality management standards. This study aims to analyze the effect of Quality Assurance on customer loyalty mediated by customer satisfaction at the Horison GKB Hotel in Gresik, East Java. This study uses a quantitative approach. The research variables are Quality Assurance, Customer Satisfaction, and Customer Loyalty. Data collection uses communication techniques and observation techniques with survey tools and direct observation at the Horison GKB Hotel in Gresik. In this study, a sample size of 153 was used, obtained from users of the Horison GKB Hotel in Gresik, East Java, who have met the criteria as determined in purposive sampling. Data analysis uses Structural Equation Modeling with SmartPLS4 tools. The results show that Quality Assurance has a positive and significant effect on customer satisfaction and customer loyalty both directly and indirectly. This finding confirms that Quality Assurance has a strategic role in building customer loyalty in the hospitality industry.